THE IMPACT OF DYNAMIC CAPABILITIES ON THE PERFORMANCE OF BOTTLED WATER FACTORIES IN BAYELSA STATE, NIGERIA - Asaolu, Olalekan Adebowale (African Journal of Social and Behavioural Sciences, 2025)
The research investigated how dynamic capabilities affect the performance of bottled water facilities in Bayelsa State. The research utilised a cross-sectional survey design method. The study population comprises 205 employees from the factories. A sample size of 136 respondents was selected. This study used the stratified sampling technique. The research employed a questionnaire as a tool for data collection. A test-retest approach was employed to ascertain the instrument's reliability. Descriptive statistics and Spearman rank correlation were employed as the statistical tools. The outcome indicated a positive correlation between sensing capability (r = 0.668) and seizing capability (r = 0.583) with the organisational performance of water factories in Bayelsa State. This study established a strong positive correlation between dynamic capabilities (sensing and seizing) and the organisational performance of bottled water factories in Bayelsa State The study advised, among other recommendations, that companies should implement a dynamic resource allocation strategy capable of swiftly reallocating resources, including capital and personnel, to capitalise on emerging opportunities and tackle challenges that could negatively impact the performance of the factories.